2010
DOI: 10.1136/oem.2009.050849
|View full text |Cite
|
Sign up to set email alerts
|

A workplace intervention for sick-listed employees with distress: results of a randomised controlled trial

Abstract: No overall effect of the participatory workplace intervention on lasting RTW was found. The workplace intervention appeared effective on lasting RTW for employees who at baseline intended to return to work despite symptoms. For employees who showed no baseline intention to return to work, the intervention did not have any effect. Other approaches are needed for this subgroup. This trial has been registered at the Dutch National Trial Register ISRCTN92307123.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
107
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 31 publications
6
107
0
2
Order By: Relevance
“…As described before, Lambeek et al and van Oostrom et al showed the effectiveness of the intervention on time until sustainable return to work for workers sick-listed due to back pain and distress, respectively. [17,18] The participatory workplace intervention was evaluated among sick-listed workers. In the current study, we chose to include workers not (yet) sick-listed but limited in their work functioning.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described before, Lambeek et al and van Oostrom et al showed the effectiveness of the intervention on time until sustainable return to work for workers sick-listed due to back pain and distress, respectively. [17,18] The participatory workplace intervention was evaluated among sick-listed workers. In the current study, we chose to include workers not (yet) sick-listed but limited in their work functioning.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Another study showed that the intervention was effective on sustainable return to work for workers sick-listed due to distress if they intended to return to work despite symptoms. [18] The first component of the intervention is integrated care, the second component a participatory workplace intervention. [19] In addition to integrated care, we included a workplace intervention in the intervention programme, based on participatory ergonomics.…”
Section: Introductionmentioning
confidence: 99%
“…Contacts with health care are often complex with many actors involved (5,6,11), and increased communication between physicians in primary health care and occupational health services is essential (14,15). There is some evidence that collaboration between the sick-listed patient, health care providers and the employer favours the rehabilitation process (10,(16)(17)(18). Patients consider their contact with the health care provider as an important part of their rehabilitation that affects recovery and return to work (RTW) (17,(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Opinions about satisfaction and reported usefulness were found to be important measures for evaluating a RTW program based on graded activity combined with work-related interventions (7). expectations and obstacles to recovery, because preferences influence the outcome of interventions and RTW (13,18,29,30). Mergl et al (31) found that patients with depression who received the preferred intervention in primary health care (medication or psychotherapy) responded better to the intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation